Studi Empiris Faktor Determinan Prestasi Kerja Pegawai - Rita Safitri; Heri Purwanto; M. Trihudiyatmanto; M. Elfan Kaukab (Faculty of Economics and Business, University of Pancasakti Tegal, 2021)
Job performance is a result of work in quality and quantity achieved by an employee in carrying out his duties by the responsibilities that have been given to him. An employee is said to be successful in carrying out his job if the work obtained is higher than the predetermined standard. The purpose of this study was to determine and analyze the effect of training, promotion, and transfer on the work performance of the employees of the Social and Village Empowerment Service Office of Wonosobo Regency. This study uses a quantitative approach. The population of this study was all employees of the Social and Village Empowerment Office of Wonosobo Regency. Methods of data analysis using multiple linear regression. The conclusion of this study is (1) partially training has a significant effect on job performance. (2) partially, job promotion has a significant effect on work performance. (3) partially, the mutation has a significant effect on work performance. (4) simultaneous training, promotion, and transfer have a significant effect on work performance.